Getting acquainted with social networks and apps: combating fake news on social media. Issue 3 (27th July 2018) - Anderson, Katie Elson
Abstract : Purpose: The purpose of this paper is to provide a general overview of how the major social media companies are addressing the problem of fake news and the spread of digital disinformation. The fight against bad sources and false authorities is one that librarians have been engaged in for a very long time. Design/methodology/approach: While the inaccurate information may not always have been called "fake news, " misinformation, propaganda, conspiracy, exaggeration, manipulated facts and out and out lies have always been combated by librarians through information literacy. It is nearly impossible to go a day in this current news climate without reading or hearing the term "fake news"; whether it is being tweeted by the 45th president of the USA, discussed in the media, detailed in articles about social media or addressed by librarians in literature, conversation, conferences, tweets and blog posts. Findings: The inescapable phrase was named word of the year for 2017 by both the American Dialect Society ("Fake News, " 2018) and Collins Dictionary (Meza, 2017). While the official definitions provided by a number of different sources may vary, the gist of what is meant by fake news is that it is information that is largely inaccurate, misleading, unsubstantiated, manipulated or completely fabricated that is being passed off as truthful, authoritative and accurate. Originality/value: Though the phrase "fake news" may seem to be a recent term, it has actually been around since the end of the nineteenth century and it is not limited to just discussing political news according to Merriam-Webster.